A STUDY OF WEB USAGE MINING: FINDING PATTERNS IN WEB LOG DATA (International Journal of Food and Nutritional Sciences, 2022)
Web mining is the application of data mining techniques to discover patterns from the World Wide Web. Personal data of an individual on web is not only data related to personal profile but also is related to the navigation or surfing that individual do on web by using search engines. Web log is a listing of page referenced data. The data includes stuff data, face book details, warranty card, reward card, information relate to what an individual bye frequently, to the website an individual visits frequently, shop frequently etc. The sequence of clicked data can be used to know the users. All these data is stored as web log data. This data needs to be processed and analyzed to use it to know the interest of a visitor or customer to increase business. This paper gives a brief study of how a web log data is preprocessed and how patterns are formed to detect the most likely user and group of users traversing certain web pages.